Transforming Asian cities : intellectual impasse, Asianizing space, and emerging trans-localities - Perera, Nihal; Tang, Wing-shing. (London : Routledge, 2013)
'Draws attention to how Asians produce their contemporary urban practices, identities and spaces as part of, resisting, responding to and avoiding larger global and national processes. The individual chapters illustrate that'global' spaces are more (trans)local, traditional environments are more modern, and Asian spaces are better defined than acknowledged. The aim is to develop room for understandings of Asian cities from Asian standpoints, especially acknowledging how Asians observe, interpret, understand, and create space in their cities'--
Includes bibliographical references (p. [262]-284) and index.
Keywords: Cities and towns -- Asia; Sociology, Urban -- Asia